Internationalization of Education: La Peau de Сhagrin of the Russian Language - R. M. Petruneva; L. F. Belyakova; T. L. Sidorova (Высшее образование в России, 2021)
The article examines the processes of internationalization, provides information on the number of foreign students in various countries and in Russia, discusses the arguments for choosing the country for study by international students, including socio-cultural and linguistic preferences. The authors address the issues relating to the status of the Russian language in countries of the Central Asia region – the former republics of the Soviet Union. The article provides an information on the expansion of Western and Eastern countries into the educational system of these countries. The conclusion is made about the need for Russian universities to more actively enter the international market of educational services, especially in those areas where the Russian Federation has undeniable achievements (natural science fields of training, etc.).